2022
DOI: 10.1038/s41598-022-24166-w
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red blood cell aggregation and dextran molecular mass

Abstract: The aim of this study was to investigate the aggregation of red blood cells (RBCs) suspended in dextran solution at various levels of molecular mass. Dextran solutions at molecular mass 40, 70, 100 and 500 kDa at concentration from 2 to 5 g/dL were used to suspend the RBCs. The radius and velocity of sedimenting RBC aggregates were investigated using image analysis. The radius and sedimentation velocity of aggregates increased initially, then decreased after achieving maxima. The maximal velocity of RBC aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In addition to the cellular factors investigated in this study, the aggregation of erythrocytes in vivo is also influenced by plasma factors, specifically an increase in fibrinogen concentration and a rise in high-molecular-weight AOPPs. In our previous work, we demonstrated that the porosity of the formed aggregates decreases with increasing concentration of Dextran, regardless of its various molecular weights [98]. This suggests that in plasma, the effects described above may be magnified.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to the cellular factors investigated in this study, the aggregation of erythrocytes in vivo is also influenced by plasma factors, specifically an increase in fibrinogen concentration and a rise in high-molecular-weight AOPPs. In our previous work, we demonstrated that the porosity of the formed aggregates decreases with increasing concentration of Dextran, regardless of its various molecular weights [98]. This suggests that in plasma, the effects described above may be magnified.…”
Section: Discussionmentioning
confidence: 79%
“…The image analysis method used in this study involves analyzing a time series of images to estimate the velocity and size of three-dimensional RBC aggregates. These procedures are described in more detail in the publication [98,102]. To analyze the aggregate movement, the time sequences of one-pixel-wide clippings for a given column of the sample from 50 consecutive images were composed (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, the addition of HMWD to blood likewise induced RBC aggregation [159,160] and did so as well when added to RBCs in PBS [161,162]. The same RBC disaggregating effect of LMWD was observed in vitro [163], possibly caused by competitive binding to RBCs that limited bridging between adjacent RBCs by larger molecules.…”
Section: Experimentally Induced Rbc Clumping In Vivo: Parallels To Se...mentioning
confidence: 73%